T3P® mediated domino C(sp2)–H sulfenylation/annulation of enaminones and methylsulfinyls for the synthesis of chromone thioether derivatives. (9th January 2019) - Balakrishna, C.; Gudipati, Ramakrishna; Kandula, Venu; Yennam, Satyanarayana; Uma Devi, P.; Behera, Manoranjan
Abstract : Regio-selective preparation of 3-sulfenylated chromone using T3P® has been described for the first time. Abstract : A new regioselective method for the synthesis of 3-(methylthio)-4 H -chromen-4-one and 3-(phenylthio)-4 H -chromen-4-one derivatives has been developed. The reaction between o -hydroxy-phenyl-functionalized enaminones and methylsulfinyl derivatives using T3P® gave good yields of chromone thioether derivatives. The reaction proceeds via domino chromone ring construction and C(sp 2 )–H bond sulfenylation under transition-metal-free conditions.